THE APPLICATION OF MICROELECTRODES TO THE STUDY OF PHOTOCHEMICAL-REACTIONS - Compton, R; Eklund, J; Nei, L (1995)
The use of microelectrodes for the study of the kinetics and mechanism of photoinduced processes is described with reference to two examples. First, the rate of light-induced electron transfer between anthraquinone and the tetraphenylborate anion is quantified using phototransient experiments at microband electrodes and the resulting data are shown to be in good agreement with independent measurements. Second, microdisc experiments are used to characterize the rate of photofragmentation of electrogenerated radical anions of 1-bromoanthraquinone. Again, comparison with independent measurements shows excellent agreement. Finally the ability of using microelectrodes for quantitative voltammetry in the near absence of supporting electrolyte is exploited to demonstrate that in the photoelectrochemical reduction of 1-bromoanthraquinone to anthraquinone the source of the required H atoms is the supporting electrolyte. © 1995.